2015
DOI: 10.1056/nejmoa1501917
|View full text |Cite
|
Sign up to set email alerts
|

Early Inhaled Budesonide for the Prevention of Bronchopulmonary Dysplasia

Abstract: BACKGROUND Systemic glucocorticoids reduce the incidence of bronchopulmonary dysplasia among extremely preterm infants, but they may compromise brain development. The effects of inhaled glucocorticoids on outcomes in these infants are unclear. METHODS We randomly assigned 863 infants (gestational age, 23 weeks 0 days to 27 weeks 6 days) to early (within 24 hours after birth) inhaled budesonide or placebo until they no longer required oxygen and positive-pressure support or until they reached a postmenstrual ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
190
2
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 228 publications
(209 citation statements)
references
References 29 publications
4
190
2
7
Order By: Relevance
“…Because of safety issues with systemic dexamethasone, lungtargeted alternatives to corticosteroid therapy have been explored. Administration of inhaled budesonide has generally been ineffective (6), likely because of inefficient delivery to the lung parenchyma, although a recent trial with prolonged treatment demonstrated reduced BPD occurrence (7). Pilot studies performed by Yeh and colleagues (8,9) used intratracheal instillation of budesonide suspended in surfactant to improve the delivery of budesonide to the lung periphery.…”
Section: Clinical Relevancementioning
confidence: 99%
“…Because of safety issues with systemic dexamethasone, lungtargeted alternatives to corticosteroid therapy have been explored. Administration of inhaled budesonide has generally been ineffective (6), likely because of inefficient delivery to the lung parenchyma, although a recent trial with prolonged treatment demonstrated reduced BPD occurrence (7). Pilot studies performed by Yeh and colleagues (8,9) used intratracheal instillation of budesonide suspended in surfactant to improve the delivery of budesonide to the lung periphery.…”
Section: Clinical Relevancementioning
confidence: 99%
“…Inhaled steroids did not reduce BPD and death, failure to extubate or the total duration of mechanical ventilation or oxygen dependency [17]. The Neonatal European Study of Inhaled Steroids (NEUROSIS) randomised trial compared the effects of inhaled budesonide to placebo administered in the first 24 hours in 863 infants born at 23 to 27 weeks gestation who required some form of positive-pressure support [18]. The intervention was delivered until the infants no longer required supplementary oxygen or positive pressure support or were a postmenstrual age (PMA) of 32 weeks.…”
Section: Corticosteroidsmentioning
confidence: 99%
“…The intervention was delivered until the infants no longer required supplementary oxygen or positive pressure support or were a postmenstrual age (PMA) of 32 weeks. Inhaled budesonide administration was associated with significant reductions in the rate of BPD, surgical closure of a patent ductus arteriosus (PDA) and reintubation , but there was a trend towards increased mortality (16.9% versus 13.6%) [18].…”
Section: Corticosteroidsmentioning
confidence: 99%
“…В большом рандомизированном исследовании показано, что раннее (в течение 24 ч после рождения) интратрахе-альное введение будесонида снижает частоту БЛД у глубо-ко недоношенных новорожденных с гестационным возрас-том менее 28 нед -до 28 против 38% в группе плацебо [56]. Продемонстрировано увеличение частоты удачной экстубации при использовании ингаляторного будесонида без снижения частоты формирования БЛД [57].…”
Section: медикаментозное лечение детей с бронхолегочной дисплазиейunclassified